Decline of large-diameter trees in a bamboo-dominated forest following anthropogenic disturbances in southwestern Amazonia - Ziccardi, Leonardo Guimarães; Graça, Paulo Maurício Lima Alencastro de; Figueiredo, Evandro Orfanó; Fearnside, Philip Martin (Annals of Forest Science, 2019)
Key message: Reduction in the aboveground biomass of larger trees is the main consequence of disturbances in open forests dominated by bamboo. Because these trees are of central importance both for ecosystem function and for the economic value of the forest for management, the impact on these trees due to the increase of bamboo abundance following anthropogenic disturbances is both an environmental and a commercial concern. Context: Bamboo-dominated forests in southwestern Amazonia are increasingly exposed to the combined impacts of fire and selective logging. Although the climbing bamboos (Guadua spp.) are considered native species of these forests, disturbances contribute to a discontinuous canopy, which is an ideal scenario for an increase in abundance of these opportunistic plants. The regeneration of tree biomass is limited in these cases, decreasing the carbon stock of the forest. Aims: This study compares changes in bamboo abundance and forest structure in the face of forest fire and post-burn logging in the municipality (county) of Rio Branco, Acre state, Brazil. Methods: The study was conducted on the Transacreana Highway (AC 090) in the eastern portion of Acre state, Brazil. We compared changes in bamboo abundance and aboveground biomass (AGB) of an area of forest with no known recent disturbances to areas in the same forest that had been disturbed by fire and post-burn logging, which are frequent sources of disturbance in this region. The live and dead AGB values were estimated by field inventory in 2016, which was 11 years after a fire and 9 years after selective logging. The AGB values for trees and palms were estimated by allometric equations in three 2-ha areas. Bamboo abundance was expressed both by bamboo biomass (Mg ha−1) and culm density (culms ha−1), sampled by direct measurements in three 200-m2 areas. Results: Bamboo abundance was over 20% higher in forest that had been burned but not logged, as compared to undisturbed forest. Compared to undisturbed plots, aboveground forest biomass (live + dead) was 34% lower in plots exposed to fire but not logging, and 36% lower if exposed to both. Live trees and palms represented 77% of the total forest biomass (live + dead), and almost a half of this contribution (41%) was in individuals in the largest diameter class (diameter at breast height > 50 cm). Conclusion: Increase in the level of impact led to a reduction in aboveground carbon stock of the forest. One of the main consequences of disturbances in open forests dominated by bamboo is reduction of live trees and palms, especially in the diameter at breast height (DBH) class over 50 cm. © 2019, INRA and Springer-Verlag France SAS, part of Springer Nature.
Keywords: Aboveground Biomass; Abundance; Allometry; Anthropogenic Effect; Bamboo; Carbon Sequestration; Dominance; Environmental Disturbance; Forest Fires; Logging (timber); Acre [brazil]; Rio Branco [acre]; Bambusa; Guadua